Idiopathic Orbital Inflammation Syndrome: A Case Report. Issue 3 (August 2016) - Azarpira, Negar; Bageri, Babak; Rasekhi, Ali; Geramizadeh, Bita
Abstract : Idiopathic orbital inflammation syndrome is a rare inflammatory disease, with unknown etiology. We present a 72-year-old man with unilateral medial rectus mass lesion. Histologically, the mass composed of dense fibrotic tissue with infiltration of lymphocytes, plasma cells, and few eosinophils. Management was done by surgical debulking with good result and no complications.